Body temperature in baseball umpires wearing cooling vests during activity - McDermott, B. P.; Erickson, S. M.; Sroufe, A. M.; Letendre, M. A. (Journal of Athletic Training, 2013)
Exertional heat illness remains a potential for those employed in environmental extremes. Baseball umpires have attempted external mechanisms to assist body temperature maintenance during activity. Previous research on preventive cooling vests (CV) and thermoregulation have focused on moderate to severe temperature differences at the modality-skin interface. Objective: Determine effectiveness of CV that creates a minor thermal gradient at the modality-skin interface on body temperature and thermal sensation responses in baseball umpires during work. Design: Observational field study. Setting: Single Arizona fall league baseball season (92.6 ± 3.5°F, 13 ± 7%RH). Patients or Other Participants: 12 baseball umpires (183.9 ± 6.5cm, 95.5 ± 9.6kg, 23.8 ± 4.7 % body fat) rotated coverage between 3 stadiums and voluntarily participated. Interventions: Participants were randomly assigned to wear a CV (HTFx, Inc., Melbourne, FL) that changes phase at 50°F or no vest (NV) under normal padding and uniform umpiring. Subjects took an ingestible thermistor to quantify gastrointestinal temperature (TGI) at least 5 hours prior to data collection. Umpires reported to a researcher located near a dugout every ½-inning for TGI and thermal sensation assessment. Data collection included 20 total games and analysis was run on 18 plate umpire (PUM) and 48 field umpire (FUM) games. Main Outcome Measures: TGI, thermal sensation, and average increase in TGI for every ½-inning. Repeated measures ANOVAs were used to analyze treatment differences. Independent t-tests were used to identify differences in average TGI increases. Alpha was set a priori at d"0.05. Results: TGI was significantly increased compared to pre-game at every time point after 1.5 innings in PUM (pd".042) and FUM (pd".001). TGI was consistently lower, although not significantly (p=.469), with CV (100.40 ± 0.19°F) compared to NV (100.59 ± 0.19°F) in PUM. Similarly, FUM demonstrated non-significant TGI differences (CV: 100.13 ± .12°F; NV: 100.27 ± 0.13°F; p=.428). On average, TGI was 0.19°F and 0.14°F less with CV than NV for PUM and FUM, respectively. There was a significant attenuation in the average increase in TGI in PUM with CV versus NV (p=.038), but not FUM (p=.236). Thermal sensation was significantly increased after 5.5 innings compared to pre-game in PUM (pd".025), and after 0.5 innings in FUM (pd".001). Thermal sensation was significantly decreased with CV in FUM (CV: 5.2 ± 0.1; NV: 5.6 ± 0.1;p=.032), but not PUM (CV: 5.1 ± 0.2; NV: 5.6 ± 0.2; p=.150), despite a larger mean difference (PUM: 0.5 vs. FUM: 0.4). Conclusions: CV provided favorable results in preventing a rise in TGI in PUM. FUM demonstrated positive, but not significant advantages. Future research is warranted using CV on participants engaging in more intense exercise and with greater thermoregulatory challenge to determine clinical applicability of CV.